2007
DOI: 10.1128/aem.00436-07
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Immune Responses in Mice after Intragastric Administration of Lactobacillus casei Producing Porcine Parvovirus VP2 Protein

Abstract: Lactobacillus casei ATCC 393 was selected as an antigen delivery vehicle for mucosal immunization against porcine parvovirus (PPV) infection. A 64-kDa fragment of PPV major protective antigen VP2 protein was used as the parvovirus antigen model. A recombinant Lactobacillus expressing VP2 protein was constructed with plasmid pPG611.1, where expression and localization of the VP2 protein from recombinant Lc393-rPPV-VP2 was detected via sodium dodecyl sulfate-polyacrylamide gel electrophoresis, Western blotting, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…However, public fear of using an attenuated pathogen as a vaccine carrier has deterred its acceptance. Recent studies have shown that oral administration of a number of lactobacilli expressing recombinant immunogens induces local mucosal (42) and systemic antibody responses (62). Other studies have explored this further and showed that immune responses induced via lactobacilli delivered through oral vaccination confer some protection against challenge with the respective pathogen (27,31,32,60).…”
Section: Discussionmentioning
confidence: 99%
“…However, public fear of using an attenuated pathogen as a vaccine carrier has deterred its acceptance. Recent studies have shown that oral administration of a number of lactobacilli expressing recombinant immunogens induces local mucosal (42) and systemic antibody responses (62). Other studies have explored this further and showed that immune responses induced via lactobacilli delivered through oral vaccination confer some protection against challenge with the respective pathogen (27,31,32,60).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HA 1 is an important target for vaccine development. Lactobacillus is widely used as a live vaccine vehicle against various microbes (1,7,35). Accordingly, we constructed a recombinant plasmid, pLEM415-PHA 1 , and recombinant lactobacillus strains, LA4356-pH and DLD17-pH, that produce the HPAI virus protective antigen HA 1 .…”
Section: Discussionmentioning
confidence: 99%
“…To meet the need for stable recombinant VLPs of PPV, several expression systems were tested as an alternative to baculovirus expression system that is a major source of the antigen for the market [26]. E. coli [23], Lactobacillus casei [21], and recently yeast Pichia pastoris [27] were reported to have been successfully used for producing PPV VP2 protein, but VLP formation in these expression systems has not been confirmed. To our knowledge, our study provides the first evidence of stable recombinant PPV VP2 VLPs not produced in baculovirus expression system.…”
Section: Expression and Purification Of Ppv Vp2 Vlps In Yeastmentioning
confidence: 99%
“…These loops are shown to possess many B-cell epitopes and can tolerate insertions [19,20] that make PPV VP2 a potential antigen carrier and play a key role in PPV diagnosis and immune prophylaxis [21]. The structure of PPV capsid composed of baculovirus system generated recombinant VP2 is available in 3.5Å resolution (PDB Accession Number 1K3V) [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation